(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Landscape transformation process for the study area has been analyzed for three decades. The change of each class has been studied and attempt has been made to find out the reasons of changing pattern. The change dynamics were not same all over the study area, so for detail analysis the whole basin has been classified into three different zones (High, Medium and Low land) on the basis of elevation as adopted by Soil Resources and Development Institute (SRDI) of Bangladesh. Human settlement has been changed more actively in High land (Zone 1), on the other hand Small area built-up has been changed more actively in Medium land (Zone 2). These two classes have been changed positively. Forest has been changed negatively in High land (Zone 1) compared to other two zones (Medium land and Low land). Urban area has been changed to Medium land (Zone 2) as it is very near to Dhaka city. Another significant positive change has been found in Brick field area in low land (Zone 3) along the main stream of Turag river, and the reason for this is the easy transportation of bricks to Dhaka city and around by river transportation. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22219 Environ. Sci. & Natural Resources, 7(2): 115-125 2014